280 COMPARISON OF THE DRUG-SUSCEPTIBILITY PROFILE OF STAPHYLOCOCCUS AUREUS AMONG THE ADULT AND PEDIATRIC POPULATIONS, 2001-2006. Issue 1 (1st January 2007) - Ebert, V.; Afghani, B.
Abstract : Drug-susceptibility profile of Staphylococcus aureus is changing rapidly. Comparative data on drug susceptibility patterns of S. aureus in adult and pediatric population are scant. Objective: To compare the drug-susceptibility profile of S. aureus in the adult and pediatric population hospitalized at the University of California, Irvine Medical Center (UCIMC). Methods: We analyzed drug susceptibility of all patient isolates of S. aureus recovered from various clinical sources for patients hospitalized at UCIMC between January 2001 and July 2006. Results: Drug susceptibility of 2, 268 patient isolates was reviewed and compared for the pediatric (0-18 years old) and the adult (> 18 years old) population (see Table ). Adults were more likely to have methicillin-resistant S. aureus (MRSA) isolates compared with the pediatric population for both periods (2001-2003 vs 2004-2006). Clindamycin resistance increased between the two periods, especially for the pediatric population ( p < .05). When comparing MRSA and MSSA susceptibility profiles, MRSA isolates were more likely to be resistant to multiple antibiotics ( p < .01). Of 832 MRSA, 96% were Erythro-R and 54% were Clinda-R, whereas for 1, 436 MSSA isolates, 25% were Erthro-R and 9% were Clinda-R. D-test was performed on all isolates starting August 6, 2004. During this period, of 322 isolates (from all age groups) that tested Erythro-R and Clinda-S initially, 135 (42%) had inducible clindamycin resistance. For the pediatric population, D-test was positive for 26 (37%) of 71 Erythro-R isolates that initially tested Erythro-R and Clinda-S. Conclusions: At our center, the drugsusceptibility pattern of S. aureus is different in adult and pediatric populations and has changed over time. A significant proportion of the Erythro-R S. aureus has inducible clindamcycin resistance. Further analysis will include review of susceptibility profiles according to the specimen type and mode of transmission of S. aureus (community vs health care associated).